The Ideology of Contemporary Islamic Education: Foundations of Thought at 3 Islamic Educational Institutions in Yogyakarta - Sodiq, Ali; Siregar, Maragustam; Maksudin, Maksudin; Shaleh, Shaleh (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study aims to discuss the ideological form of contemporary Islamic education in Indonesia. This study investigates the phenomenology of three Yogyakarta school institutions. Design/methods/approach – This is a qualitative study with a phenomenological pedagogical approach. This study focuses on three Islamic educational institutions in the Special Region of Yogyakarta: Madrasah Aliyah Unggulan (MAU) Al-Imdad Bantul Yogyakarta, Madrasah Mu’allimin Muhammadiyah (M3) Yogyakarta, and SMAIT Abu Bakar Yogyakarta. Purposive sampling and snowball techniques were used to select the informants. Findings – This study found that Al-Imdad Superior Madrasah Aliyah was an educational advancement from Nadlotul Ulama. The educational ideology of the Al-Imdad Superior Aliyah Madrasah is conservative-religious. Madrasah Mu’allimin Muhammadiyah is a Muhammadiyah cadre school with a fundamental conservatism ideology. SMAIT Abu Bakar has a fundamentalist-conservative ideology and a formalistic-revivalist religious attitude. Research implications/limitations – This study only looks at the ideological perspectives of Islamic educational institutions. The results of this study can be used to make recommendations to policymakers, particularly the Ministry of Religion of the Republic of Indonesia, in determining the direction of future development of Islamic educational institutions. However, this study only looks at the aspect of thinking. Further research can concentrate on the managerial aspects of each Islamic educational institution. Practical implications – The results of this study shed light on the various characteristics of Islamic educational institutions in Indonesia. In theory, this research has implications for developing an Islamic thought map regarding existing Islamic educational institutions. This study also provides insight into Indonesia’s ideological diversity of Islamic educational institutions.